Pengaruh Value Orientation dan Personality terhadap New Environmental Paradigm Siswa - Ervina Dwi Puspita; I Made Putrawan; Mieke Miarsyah (Universitas Negeri Jakarta, 2021)
The development of paradigm from anthropocentric to new environmental paradigm is necessary. Students have to possess the new environmental paradigm in order to protect the environment. Students new environmental paradigm can be affected by several factors such as value orientation and personality. This study aimed to determine the effect of value orientation and personality on the new environmental paradigm that students have. This study was hold in a first term of 2019/2020 school year at SMA Negeri 4 Kota Bekasi. The method used is the survey with quantitative-causal causal approach and path analysis. The sample is 95 students of XI MIPA which selected randomly. There were three instruments used for measuring new environmental paradigm, value orientation and personality with reability of 0.691, 0.809, and 0.864. As a result of study, personality is suitable as mediator of variables between value orientation and new environmental paradigm.